The development of a brief version of the Lexington Attachment to Pets Scale (Brief-LAPS) - Lund, Thomas Bøker; Corr, Sandra A.; Hirschhofer, Viktoria; Sandøe, Peter; Serpell, James; Springer, Svenja (Frontiers in Veterinary Science, 2025)
Several questionnaire-based instruments have been developed to measure pet owners' attachments to their pets, but they are often lengthy, which likely limits their use in studies where respondent fatigue and data collection costs are concerns. One of these is the Lexington Attachment to Pets Scale (LAPS) which has been increasingly used in recent years. It consists of 23 items addressing owners' levels of attachment to their pets. A total attachment score (full LAPS), and 3 sub-scores on the sub-dimensions of General Attachment, People Substitution, Animal Rights/Welfare, can be calculated. The current paper describes the development of a brief-version of the LAPS (Brief-LAPS). We first provide an overview of existing research where the LAPS is used. Then, to develop the Brief-LAPS, we use a combination of input from experts in human-animal interaction (n = 54) about the content validity of the 23 items, and analysis of measurement invariance on questionnaire data from cat and dog owners in 3 European countries [Austria, Denmark, and the UK (n = 2,037)]. Sixteen of the 23 original items were removed, leaving a 7-item Brief-LAPS scale where items from all 3 sub-dimensions are represented. The Brief-LAPS is intended to replace the full LAPS, and it does not offer brief versions of the 3 sub-dimensions. The full and Brief-LAPS are highly correlated (Pearson's r = 0.95). Also, patterns of associations between the full LAPS and a range of measures of interest in practical research are highly similar when running the same associational analyses with the Brief-LAPS. For future users, the paper provides scoring instructions for the Brief-LAPS, including how to calculate a composite score (range: 0–21). We recommend the use of the Brief-LAPS for studies in which questionnaire burden and data collection costs are a concern, but not when mean comparisons with the full LAPS are of interest, or when one or more of the LAPS sub-dimensions are of interest. Scholars should use caution when comparing the Brief-LAPS scores between countries. We recommend additional psychometric evaluations particularly in non-Western countries, to ensure that the Brief-LAPS scale is psychometrically sound beyond the three countries studied in this paper.